Mosaic of flowering decorations in Syria during the Byzantine period (Damascus University Journal of arts and humanities sciences, 2021)
The Mosaic is an architectural decorative art, which used at livery the floors of palaces and Roman villas and in the churches after the apperance of christianrelegion.The artist varies the topics, which used at the mosaics, in the beginning he depends onmethology sights and with in the Christian religion Spread that topics were forbidden and replaced by geometric, botanic and animal sights.In our research, we will provide abstract about one sort of grounds mosaic, which are  called the carpeting mosaics that depend on different finds of  nature centered flowers, which a ccompaning with animal sights or geometric decorations, or form the major of mosaic field.These flowrs are distributed in parallel lines or random form, but at the  two conditions they must be in the whole floor.These mosaics are made in our examples by two ways: first it is executed by parallel and verticals cubes, with intend colours to form the board.The second: one the boared is executed by compacting cubes with curved style to give the scaly style, in each squama we can notice the  nature centered flowers give the required ground.
Keywords: Mosaic of flowering decorations in Syria during the Byzantine period